Effect of Aromatherapy Applied in Pallıatıve Treatment on Management of Nausea and Vomiting Symptoms - Mariyana, Rina; Hasnita, Evi; Febrina, Cory (PT. Riset Press International, 2024)
Despite advances in the diagnosis and treatment of cancer, patients still suffer from the various physical and psychological complications of cancer. Patients in palliative care often experience symptoms such as nausea, vomiting, anxiety, sleep disturbances, and pain. Managing the symptoms experienced by patients is important in improving the patient's quality of life. Effective management of these symptoms can be done by applying complementary therapies. In this regard, papermint aromatherapy can be used as a potential complementary treatment for symptom management in palliative care. This study aimed to determine the impact of papermint aromatherapy applied to patients in palliative care on the management of symptoms of nausea and vomiting. This research uses quasi-experimental research (single group study without a control group. One-Group Pretest Posttest research design is a measurement before and after treatment. The tool used in this research is a scale for assessing symptoms of nausea. The instrument used for variables dependent, namely to measure the intensity of nausea and vomiting felt by the client using the Rhodes Index for Nausea, Vomiting, and Retching (INVR). The nausea and vomiting scale at 0 indicates no nausea and vomiting, scale 1 indicates mild nausea and vomiting moderate, scale 3 indicates severe nausea and vomiting, and scale 4 indicates severe nausea and vomiting. For the independent variable, use the observation sheet. Findings revealed this study showed significant changes in scale scores, indicating the effectiveness of papermint aromatherapy on symptoms of nausea and vomiting commonly encountered in palliative care. The use of aromatherapy with papermint to treat nausea and vomiting has a p value of 0.027%. Based on this research, parents need to receive information about children with good delivery techniques, according to parents' needs, honestly, openly, in more detail about the child's condition and in accordance with procedures.